Competency Achievement of Community Medicine at Tutorial Discussion, Analysis Congruence Faculty Learning Objective and Achieved Learning Objective - Pratama, Henry Aldezzia; Probandari, Ari Natalia; Timor Randita, Amandha Boy (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2017)
Background: The high rate of remediation at Community Medicine Block still occur in Medical School Universitas Sebelas Maret, which has the vision and mission of producing graduates who are community oriented. On the block, the learning activities in the form of tutorial discussions, lectures support, skills lab, and field lab. Tutorial discussions can be considered as a core in the model of Problem Based Learning (PBL). In the tutorial discussions, students will look for their own learning goals, known as the Achieved Learning Outcome (ALO), while the faculty to design Faculty Learning Objective (FLO) is expected to achieve student. This study aims to determine the description of the achievement of community medical competence with the analysis FLO and ALO congruence in tutorial process. Methods: This research is descriptive qualitative research. This research was conducted at the Faculty of Medicine, Universitas Sebelas Maret Surakarta in September-November 2016. This study used a total sampling on report tutorial of the 2nd scenario of Community Medicine, as many as 20 reports. Data were collected through Examining records (checking of documents). Data analysis was performed through discourse analysis. Result: Researchers obtained 15 statements tutorial, with 11 reports softfile and 4 reports hardfile. The congruence of FLO and ALO varied on each FLO. Two FLO achieved 100% by a group tutorial, whereas in other FLO, there is group with ALO only partially met by FLO. There is 1 FLO majority is not reached. ALO about family physicians appear on the 12 of report which actually not listed in FLO. Conclusion: The achievement of FLO varies in each FLO, with also found ALO incongruent with FLO in the majority of the group tutorials. Further research on the factors that influence the achievement of FLO and other aspects of learning in the block needs to be done to determine competency achievement. Evaluation should always be done either on the side of the scenario, tutors, and students for achievement of learning objectives tutorial. Keywords: ALO, FLO, congruence, tutorial, competency